Dielectric properties of epoxy/montmorillonite nanocomposites and nanostructured epoxy/SiO2/Montmorillonite Microcomposites. Issue 1 (21st August 2014) - Couderc, Hugues; Fréchette, Michel; David, Éric; Savoie, Sylvio; Guastavino, Francesco; Thelakkaday, Abdul Salam; Coletti, Gianfranco; Fina, Alberto
Abstract : Composites reinforced with microparticles using a polymer matrix reinforced by nanoparticles represent a new emerging class of materials. Epoxy composites have been prepared using quartz as microfillers and organically modified Montmorillonite as nanofillers in order to study the dielectric properties of such new materials. The structure of the composites as determined by transmission electron microscopy, is neither exfoliated nor intercalated, although the thickness of C30B stacks is in the nanometric range. The influence of nano‐ and microparticles on epoxy matrix amorphous structure has been highlighted through Differential Scanning Calorimetry experiments. C30B has not effect on glass transition temperature but a drastic from 357 K to 325 K decrease is observed with the addition of microparticles. Heat capacity step remains unchanged, except for the microcomposite. And finally, Broadband Dielectric Spectroscopy has been used to characterize the dielectric properties at different temperatures. The spectra have been fitted with Havriliak–Negami equation to extract the relaxation times and the dielectric strengths associated with local β and γ relaxations and the main α relaxation. POLYM. COMPOS., 115–124, 2016. © 2014 Society of Plastics Engineers